Perceptions of the Post First-Lockdown Era in the Current Covid-19 Pandemic: Quantitative and Qualitative Survey of the French Population - Fouques, Damien; Castro, Dana; Mouret, Marion; Julien-Sweerts, Sabrina; Romo, Lucia (Frontiers in Psychology, 2021)
Introduction: A pandemic with the severity of COVID-19 affects people’s lives physically, as well as their daily routines, views of the world, and emotional balance. Lockdown is often an unpleasant experience due to a separation from loved ones, loss of freedom, and uncertainty over the disease status. To adjust, individuals and groups have had to adapt their perceptions of the event to the current scenario. This study aims to describe the perceptions of confined people on the changes occurring in their lives in the aftermath of the COVID-19 lockdown. Methods: A total of 1534 individuals (26.6% men; 73.4% women; mean age 41.6) responded to the questionnaire comprising 19 closed and five open-ended questions about the changes they anticipated in their lives in the immediate post-confinement era. Results: Two definite groups appeared in the results: those who lived the confinement pleasantly, and those for which it was painful. They differ according to their confinement conditions and perceived degree of exposure to the virus. There seems to be a link for those who had a pleasant experience to a lower perceived exposure to the virus and less burdensome confinement conditions (young children, surface area, etc.). Lockdown conditions seem to influence the respondents’ perceptions: a pleasant experience is associated with a vision of the society’s evolution at large, and the care about its economic and professional progress; a painful one is associated more with focusing on the immediate needs of social support and personal wellbeing. Discussion: Emotional experience during lockdown impacts the perception of its aftermath, with hope and anxiety becoming two ways of coping with uncertainty.